Forevermore - Hake, Cathy Marie (Bethany House, 2008)
Hope Ladley helps cook for the field hands during the harvest, and her sunny disposition and unstinting love make changes of a different kind in widower Jakob's home, but when Jakob's abusive brother-in-law shows up, he threatens the newfound happiness of the farm.